Analisis Faktor Penentu dalam Pemilihan Indekos Mahasiswa di Surabaya: Studi dengan Pendekatan Mixed-Method - Prihono, Prihono; Nurcahyanie, Yunia Dwie (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2024)
This study examines the factors influencing students' decisions in selecting boarding houses in Surabaya, an increasingly critical issue as demand for student housing rises post-pandemic. A mixed-method approach was employed, beginning with open-ended questionnaires to identify broad preferences, followed by closed-ended questionnaires to rank key factors. Factor analysis using SPSS revealed three dominant factors: security and environment (33.79%), location and price (22.19%), and facilities (20.47%). Among these, security and environment emerged as the most influential, underscoring the importance of safety and a clean, comfortable setting. Location and price ranked second, with students favoring affordable boarding houses near campuses and essential services. Facilities, including high-speed internet and clean sanitation, also significantly impacted decisions. These findings offer practical insights for boarding house owners to prioritize safety measures, enhance cleanliness, and improve facilities to attract students. While the results align with existing literature on housing preferences, this study is limited by its sample size and focus on Surabaya, which may not generalize to other contexts. Future research could explore additional factors such as parking availability or shared amenities and extend the analysis to other cities for comparative insights. This research contributes to understanding student housing preferences and offers actionable recommendations for managing boarding houses in urban educational hubs.